Wage-setting in the Hospital Sector - Buchan, James (OECD Health Working Papers, 2014)
This paper examines wage setting mechanisms for health workers in hospitals across eight different OECD countries. It describes similarities and differences and how fixed or fluid these approaches have been in recent years through health system reforms, labour market dynamics and economic pressures. Based on a review of grey literature and expert interviews with officials from the covered countries, it finds that prior to the economic downturn, several countries had signalled a shift to more local and flexible wage setting in the hospital sector but this ambition does not seem to have been realised in full for public sector hospitals in most OECD countries. Fiscal pressures have led to some "recentralisation" of wage setting, particularly in France, Portugal and the United Kingdom. While the extent of centralisation has been a question of considerable debate, the countries covered in this paper suggest that the benefits of centralised and/ or co-ordinated wage setting generally appear to have been given more attention by policy makers. The current research base on the effectiveness of different wage setting approaches is limited. Policy-making would benefit from developing a better understanding of the impact of wage setting on improved hospital performance and quality